Molecular and clinical delineation of 2p15p16.1 microdeletion syndrome. Issue 8 (1st June 2017) - Lévy, Jonathan; Coussement, Aurélie; Dupont, Céline; Guimiot, Fabien; Baumann, Clarisse; Viot, Géraldine; Passemard, Sandrine; Capri, Yline; Drunat, Séverine; Verloes, Alain; Pipiras, Eva; Benzacken, Brigitte; et al.
Abstract : Interstitial 2p15p16.1 microdeletion is a rare chromosomal syndrome previously reported in 33 patients. It is characterized by intellectual disability, developmental delay, autism spectrum disorders, microcephaly, short stature, dysmorphic features, and multiple congenital organ defects. It is defined as a contiguous gene syndrome and two critical regions have been proposed at 2p15 and 2p16.1 loci. Nevertheless, patients with deletion of both critical regions shared similar features of the phenotype and the correlation genotype–phenotype is still unclear. We review all published cases and describe three additional patients, to define the phenotype–genotype correlation more precisely. We reported on two patients including the first prenatal case described so far, carrying a 2p15 deletion affecting two genes: XPO1 and part of USP34 . Both patients shared similar features including facial dysmorphism and cerebral abnormalities. We considered the genes involved in the deleted segment to further understand the abnormal phenotype. The third case we described here was a 4‐year‐old boy with a heterozygous de novo 427 kb deletion encompassing BCL11A and PAPOLG at 2p16.1. He displayed speech delay, autistic traits, and motor stereotypies associated with brain structure abnormalities. We discuss the contribution of the genes included in the deletion to the abnormal phenotype. Our three new patients compared to previous cases, highlighted that despite two critical regions, both distal deletion at 2p16.1 and proximal deletion at 2p15 are associated with phenotypes that are very close to each other. Finally, we also discuss the genetic counseling of this microdeletion syndrome particularly in the course of prenatal diagnosis.